(untitled) (International Association of Biologicals and Computational Digest, 2023)
Salvadora oleoides L. is a facultative and mesomorphic xerophyte adapted to arid and semi-arid regions. It is commonly known as meetha jal in Gujarat and Rajasthan. These plant species populations were grown in different ecological regions such as Punjab, Rajasthan, and Kutch. The present study analyzed the presence of secondary metabolites and also their amount. The anti-oxidant assay such as DPPH and ABTS determine the reducing agent which is present in plant. Anti-bacterial activity checked against the pseudomonas bacteria is 5 mm (Zone of inhibition) at concentration of 1 mg/ml.